Well, that's freaky!

Calculus Level 4

Compute r = 1 2 2 r 1 ( 1 ) r ( 2 r ) ! . \large\displaystyle\sum_{r=1}^{\infty} \frac{2^{2r-1}(-1)^r}{(2r)!}.

Give your answer to 3 decimal places.


The answer is -0.708.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Anish Puthuraya
Nov 25, 2015

cos ( x ) = 1 x 2 2 ! + x 4 4 ! \cos(x) = 1 - \frac{x^2}{2!} + \frac{x^4}{4!} - \ldots

cos ( 2 x ) = 1 2 2 2 ! x 2 + 2 4 4 ! x 4 \cos(2x) = 1 - \frac{2^2}{2!} x^2 + \frac{2^4}{4!} x^4 - \ldots

1 + cos ( 2 x ) = 2 2 2 2 ! x 2 + 2 4 4 ! x 4 1+\cos(2x) = 2 - \frac{2^2}{2!} x^2 + \frac{2^4}{4!} x^4 - \ldots

1 + cos ( 2 x ) 2 = 1 2 2 ! x 2 + 2 3 4 ! x 4 \frac{1+\cos(2x)}{2} = 1 - \frac{2}{2!} x^2 + \frac{2^3}{4!} x^4 - \ldots

Substitute x = 1 \displaystyle x=1 to get,

1 + cos 2 2 = 1 + ( 2 2 ! + 2 3 4 ! ) \frac{1+\cos 2}{2} = 1 + \left(-\frac{2}{2!} + \frac{2^3}{4!} - \ldots\right)

Hence, we have the required sum as,

2 2 ! + 2 3 4 ! 2 5 6 ! + = ( 1 + cos 2 2 ) 1 = 0.708 -\frac{2}{2!} + \frac{2^3}{4!} - \frac{2^5}{6!} + \ldots = \left(\frac{1+ \cos 2}{2}\right) -1 = \boxed{-0.708}

Anish Puthuraya , we really liked your comment, and have converted it into a solution. If you subscribe to this solution, you will receive notifications about future comments.

Brilliant Mathematics Staff - 5 years, 6 months ago
Pranav Arora
Apr 3, 2014

e 2 x = 1 + 2 x + 2 2 x 2 2 ! + 2 3 x 3 3 ! + 2 4 x 4 4 ! + \displaystyle e^{2x}=1+2x+\frac{2^2x^2}{2!}+\frac{2^3x^3}{3!}+\frac{2^4x^4}{4!}+\cdots

e 2 x 2 = 1 2 + x + 2 1 x 2 2 ! + 2 2 x 3 3 ! + 2 3 x 4 4 ! + \displaystyle \Rightarrow \frac{e^{2x}}{2}=\frac{1}{2}+x+\frac{2^1x^2}{2!}+\frac{2^2x^3}{3!}+\frac{2^3x^4}{4!}+\cdots

e 2 i 1 2 = i 2 1 2 ! 2 2 i 3 ! + 2 3 4 ! + \displaystyle \Rightarrow \frac{e^{2i}-1}{2}=i-\frac{2^1}{2!}-\frac{2^2i}{3!}+\frac{2^3}{4!}+\cdots

Notice that the sum we seek is:

( e 2 i 1 2 ) = ( cos ( 2 ) + i sin ( 2 ) 1 2 ) = ( i 2 sin ( 1 ) cos ( 1 ) 2 sin 2 ( 1 ) 2 ) = ( sin 2 ( 1 ) + i sin ( 1 ) cos ( 1 ) ) = sin 2 ( 1 ) \displaystyle \begin{aligned} \Re\left(\frac{e^{2i}-1}{2}\right) &= \Re\left(\frac{\cos(2)+i\sin(2)-1}{2}\right)\\ &= \Re\left(\frac{i2\sin(1)\cos(1)-2\sin^2(1)}{2}\right)=\Re\left(-\sin^2(1)+i\sin(1)\cos(1)\right)\\ &=\boxed{-\sin^2(1)}\\ \end{aligned}

Nice Solution. An alternative approach would be the following (well, technically, its the same solution, but anyways)

cos ( x ) = 1 x 2 2 ! + x 4 4 ! \cos(x) = 1 - \frac{x^2}{2!} + \frac{x^4}{4!} - \ldots

cos ( 2 x ) = 1 2 2 2 ! x 2 + 2 4 4 ! x 4 \cos(2x) = 1 - \frac{2^2}{2!} x^2 + \frac{2^4}{4!} x^4 - \ldots

1 + cos ( 2 x ) = 2 2 2 2 ! x 2 + 2 4 4 ! x 4 1+\cos(2x) = 2 - \frac{2^2}{2!} x^2 + \frac{2^4}{4!} x^4 - \ldots

1 + cos ( 2 x ) 2 = 1 2 2 ! x 2 + 2 3 4 ! x 4 \frac{1+\cos(2x)}{2} = 1 - \frac{2}{2!} x^2 + \frac{2^3}{4!} x^4 - \ldots

Substitute x = 1 \displaystyle x=1 to get,

1 + cos 2 2 = 1 + ( 2 2 ! + 2 3 4 ! ) \frac{1+\cos 2}{2} = 1 + \left(-\frac{2}{2!} + \frac{2^3}{4!} - \ldots\right)

Hence, we have the required sum as,

2 2 ! + 2 3 4 ! 2 5 6 ! + = ( 1 + cos 2 2 ) 1 = 0.708 -\frac{2}{2!} + \frac{2^3}{4!} - \frac{2^5}{6!} + \ldots = \left(\frac{1+ \cos 2}{2}\right) -1 = \boxed{-0.708}

Anish Puthuraya - 7 years, 2 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...